Bioinformatics Analysis to Identify Therapeutic Targets of Artocarpus altilis Compounds in Breast Cancer Therapy - Farid, Muhammad; Dewi, Fitria Puspita; Ramadhania, Widya Aryana; Rastrani, Ardestya; Rahma, Adinda Aulia (Universitas Ahmad Dahlan, 2025)
Breast cancer remains the most prevalent malignancy among women worldwide, with approximately 2.3 million new cases and 685,000 deaths reported in 2020. Despite advances in surgery, chemotherapy, radiotherapy, endocrine, and targeted therapies, these treatments are often limited by severe side effects and resistance mechanisms. Artocarpus altilis a medicinal plant rich in flavonoids and other bioactive compounds, has been traditionally utilized in various therapeutic contexts and is increasingly recognized for its anticancer potential. This study aimed to systematically identify the molecular targets and signaling pathways associated with A. Artocarpus altilis in breast cancer using a network pharmacology approach, thereby providing novel insights into its therapeutic relevance. The in-silico analysis integrated compound screening, drug-likeness evaluation, target protein prediction, protein–protein interaction mapping, Gene Ontology enrichment, and KEGG pathway analysis. Among 14 candidate compounds, three exhibited poor pharmacokinetic properties based on Lipinski’s Rule of Five. A total of 16 breast cancer-related protein targets were identified, with Epidermal Growth Factor Receptor (EGFR) and Insulin-like Growth Factor 1 Receptor (IGF1R) emerging as the most significant hubs. Functional enrichment revealed that these targets participate in critical oncogenic pathways, including PI3K/Akt, MAPK, and JAK/STAT signaling, which are strongly associated with cell proliferation, migration, and metastasis. The findings highlight the central role of EGFR and IGF1R in mediating the pharmacological effects of A. Artocarpus altilis suggesting its potential as a complementary therapeutic candidate in breast cancer management. While this study provides a systematic bioinformatics-based framework for elucidating the molecular mechanisms of A. Artocarpus altilis, further experimental validation in vitro and in vivo is essential to confirm its efficacy and safety.